(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study was undertaken to determine managers’ rating of curriculum strategies for improving school-industry linkage in vocational education in tertiary institutions in Anambra state. A research question and one hypothesis tested at 0.05 level of significance guided the study. Descriptive survey design was adopted for the study. The population of the study was 389 managers of industries located at Awka, Nnewi and Onitsha. There was no sampling because the population size was manageable. A 4-point scale validated questionnaire containing 10 items with reliability coefficient of 0.78 was used to collect data for the study. Mean ratings and standard deviation were used to answer the research question, while analysis of variance (ANOVA) was used to test the null hypothesis. Findings showed that managers of industries considered curriculum strategies important for improving schoolindustry linkage in vocational education in tertiary institutions. The researcher recommended among others that vocational institutions and curriculum designer should collaborate with industry in curriculum design for more quality content and effective program implementation